Estudio normativo, eléctrico, estructural, económico y ambiental para Solphower SAS de la implementación de un sistema fotovoltaico “Grid tie” con una capacidad mayor a 6 kw para usuario residencial del municipio de Cajicá, Cundinamarca (2020)
Solar energy has become one of the main alternatives for generating electrical energy, and as a mechanism to supply the energy supply in non-interconnected areas. This project framed photovoltaic generation, as an instrument to produce the energy that is consumed for a residential property, located in the municipality of Cajicá, whose main objective was to guarantee a reduction in the value of electrical energy consumption in monthly billing, taking Keep in mind that the implementation of projects with unconventional energy sources brings with it multiple tax benefits and that on many occasions they are unknown by the residential sectors. The use of SolidWorks modeling software and free applications for the analysis of lightning risks in the structural and electrical design phase, allowed us to analyze the geometry proposed in the structure for the support of solar panels, as well as the need for shielding of the structure, which led to a quite significant reduction in the initial investment. For the economic return, the maintenance costs produced by a photovoltaic plant were projected, as well as the economic savings that occur month by month, having the decrease in the output power of the solar modules during their useful life. Another primary aspect addressed was the environmental component, especially the reduction of greenhouse gases produced by the use of clean energy and which has been guaranteed from the legal and regulatory framework as a fundamental principle of responsibility and preservation of the environment for our future generations.